2010
DOI: 10.1583/10-3172.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Self-Expanding Stent-Graft Types on Remodeling of the Aortic Neck After Endovascular Aneurysm Repair

Abstract: Only a small number of the patients treated with self-expanding stent-grafts show notable infrarenal aortic neck dilatation, which does not appear to be related to the stent-graft model. Almost all cases of aortic neck dilatation exceeded the percentage of oversizing; less than a third of patients with aortic neck dilatation required therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, others have reported higher dilatation rates in devices with suprarenal fixation, suggesting that as an additional factor promoting dilatation. [29][30][31][32] Our cohort had few occlusive complications, occurring exclusively in patients with narrow aortic bifurcations, a known risk factor for occlusion. 33 Data for European Collaborators on Stent-Graft Techniques for Aortic Aneurysm Repair (EUROSTAR) and single-center reports further support the good performance of this device in adverse iliac anatomy, 33-35 but this was not directly evaluated in our population.…”
Section: Discussionmentioning
confidence: 92%
“…However, others have reported higher dilatation rates in devices with suprarenal fixation, suggesting that as an additional factor promoting dilatation. [29][30][31][32] Our cohort had few occlusive complications, occurring exclusively in patients with narrow aortic bifurcations, a known risk factor for occlusion. 33 Data for European Collaborators on Stent-Graft Techniques for Aortic Aneurysm Repair (EUROSTAR) and single-center reports further support the good performance of this device in adverse iliac anatomy, 33-35 but this was not directly evaluated in our population.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3] Current concepts about the reason for this phenomenon remain poorly understood, although it is known that the amount of proximal device oversizing with selfexpanding stent grafts (SESGs) influences neck progression. 4,5 Once deployed, SESGs continue to expand until the nominal diameter is reached, 6 unless tissue resistance limits expansion. 7 It has been reported that when aortic neck dilation occurs, it is related to adverse midterm outcomes.…”
mentioning
confidence: 99%
“…On the other side, a large aneurysm, co-morbidity or previous abdominal surgery would significantly increase the risks of open repair; this situation warrants the use of EVAR. Furthermore, surgeons' learning curve and advances in device technology are considerations in interpreting these results, [12][13][14] even though we did not compare these factors.…”
Section: Discussionmentioning
confidence: 98%